A Centennial of Los cuentos de mi tía Panchita (Tales of My Aunt Panchita), by Carmen Lyra (1920 - 2020): The Educational, Literary and Political Context of the First Edition - Rubio Torres, Carlos (2020)
The year 2020 commemorates one-hundred years since the Costa Rican classic, Los cuentos de mi tía Panchita (Tales of my Aunt Panchita), by Carmen Lyra and edited by Joaquín García Monge, was first published. This article sets forth some of the educational, literary and political circumstances that led to the publication of a singular literary work for children that compiled Costa Rica´s most celebrated folk tales. Emphasis is made on folklore and the importance of its publication in the children’s periodical, San Selerín, which led to the establishment of a Children’s Literature Department at the Costa Rican Teachers College and also looks at the role of the author in the different social movements that led to the fall of the Tinoco brothers´ dictatorship. The collection of stories recreates arguments previously contributed by authors Fernan Caballero from Spain and Joel Chandler Harris from the United States. Other sources are also studied, such as a compilation of popular Spanish Folk and Fairly Tales by Antonio Rodríguez Almodóvar. Even now, in the 21 century, Los cuentos de mi tía Panchita may be deemed to be politically incorrect, given its use of grammatical construction and vocabulary of conservative individuals that may be considered inappropriate for children. Yet, it is a literary work that reflects the eagerness of the author and editor to disseminate popular culture and represent their avant-garde positions.